Prevalence of enteric pathogens in HIV patients with chronic diarrhoea and their relationship with CD4 count - Sahoo, Debasish; Baral, Purabi; Mahapatra, Soumya Ranjan; Sarangi, Anshuman; K., Kiran Babu K. (International Journal of Advances in Medicine, 2018)
Background: HIV presently accounts for the highest number of deaths attributable to any single infective agent. Opportunistic infections (OIs) and associated complications account for a considerable proportion of such mortality. Diarrhoea is among the most common symptom of HIV infection. During the natural course of HIV infection, there is a progressive loss of CD4 T cells. Autors’ aim is to study the prevalence of enteric pathogens in HIV patients with chronic diarrhea and their relationship with CD4 count. Methods: We analysed 186 HIV positive patients out of which 126 had chronic diarrhea and 60 patients presenting without diarrhea as controls. The faecal samples were subjected to microscopic examination. Zeihl Neelson’s Stain for mycobacterium, Kinyoun’s acid fast stain for microsporodia, stool culture for salmonella and shigella. All patients had barium meal contrast studies, USG of abdomen and pelvis. FNAC of peripheral lymph nodes and finally CD4+ Tcell count using BD FACS. Results: Total of 68,10,01 patients of HIV diarrhoea with identifiable cause had CD4 <200, 200-250 and >350 respectively. Among HIV diarrhoea without any identifiable cause 22, 17, 08 patients had CD 4 <200, 200-250 and >350 respectively. All diarrhoeal stool samples with Isopora had CD 4 <200, M. tuberculosis 26 patients CD4 <200, 12 had 200-350 and 03 had >350. Microsporodium 03 patients had CD4 >350. Finally, among stool samples with Cyclospora, E. histolytica, Giardia and Strongyloides all patients had CD 4<200. Conclusions: The present study highlights the importance of testing intestinal pathogens in HIV. Chronic diarrhoea was more common in patients with low CD4 counts.